The relationship between the philosophy of science and technology in the development of Indonesian society - Faujian, Ares; Ahmed, Touheed; Shahzeb, Shahzeb; Sudrajat, Sudrajat (Universitas Negeri Yogyakarta, 2025)
This article explores the critical relationship between the philosophy of science and technology and their influence on the development of Indonesian society. The philosophy of science provides the framework for understanding scientific knowledge, its methodology, and its limits. Meanwhile, technology applies that knowledge practically to solve societal problems. In Indonesia, the integration of philosophy with scientific and technological progress is necessary to address the nation's cultural, ethical, and developmental challenges. This article discusses how a deep understanding of the philosophy of science can shape technological advancements in a way that promotes sustainable, equitable, and culturally sensitive development.